Perancangan Showroom dan Kafe “Chocolate Monggo” beserta Tempat Produksinya - Stefanny Muliawan; Lintu Tulistyantoro; Poppy Firtatwentyna Nilasari (Intra, 2016)
Chocolate is one kind of souvenir, which is often picked by tourists when they are travelling. Indonesia is the world’s third largest cocoa producer country. “Chocolate Monggo” is an authentic Indonesian chocolate products with the use of 100% Indonesian cocoa. Besides the used of Indonesian cocoa, “Chocolate Monggo” also employs Indonesian as their workers. This shows that “Chocolate Monggo” should be developed more. The method used for this design is problem solving method. The results of the design are showroom, café, and the production site. Showroom as a place to sell the chocolate products in packaging and souvenirs, café as a dining area for customers or visitors to enjoy small dish with a relaxed atmosphere, production site as a place to make the products. The production site can be seen by the customers or visitors, so it has the added value of education in addition to recreational facilities. The concept used is harmony which is the result of the merging of ideas derived from the meaning of the brand’s name, “Monggo”, brand’s vision, and the city where it was born.